The Influence of Ausubel’s Significant Learning on the Development of Rodari's Creative Writing Techniques (Docentes 2.0 Journal, 2020)
The research was based on the study of Ausubel meaningful learning, applying Rodari's writing techniques. The terms literary production, and creative process, are not well known in school environments. The objective of the research was to analyze the influence of Ausubel's (1963) significant learning in the development of Rodari's (1999) writing techniques with first-semester students of Social Communication - University of Pamplona. For this purpose, a bibliographic review was carried out on the relevant aspects of the theory studied, as well as the works in the international, national and regional fields, which were very useful for the methodological design, the approach of the strategy and the analysis. From the results. The type of research was qualitative with the phenomenological method, this research begins with a diagnostic stage where it was possible to establish a study population had misconceptions about literary creation, prejudices at the time of writing that prevented them from generating a creative process. After applying the information gathering techniques, after doing the analysis of the categories, it was concluded that the implementation of pedagogical strategies for meaningful learning in G. Rodari's creation techniques allows the construction of knowledge and the development of writing skills. literary in the student where he develops learning in the construction of texts through the management of techniques that enhance creativity.
Keywords: Meaningful learning; writing techniques; creative writing; literary production; creative process